2015
DOI: 10.1111/1750-3841.12885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yogurt Microstructure Using Confocal Laser Scanning Microscopy and Image Analysis

Abstract: The microstructure of protein networks in yogurts defines important physical properties of the yogurt and hereby partly its quality. Imaging this protein network using confocal scanning laser microscopy (CSLM) has shown good results, and CSLM has become a standard measuring technique for fermented dairy products. When studying such networks, hundreds of images can be obtained, and here image analysis methods are essential for using the images in statistical analysis. Previously, methods including gray level co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The above results indicated that the internal network structure of yogurt was stable and could withstand high frequency disruption, and yogurt systems showed a solid state, which was consistent with the results of Skytte et al. (2015). With the increase of frequency, tan δ decreased first and then increased, indicating that the elastic components were lost and the viscous components were gradually increased in the solid‐like yogurt system, and the elastic behavior of yogurt was gradually weakened, whereas the viscous behavior was enhanced (Zhao et al., 2013).…”
Section: Resultssupporting
confidence: 91%
“…The above results indicated that the internal network structure of yogurt was stable and could withstand high frequency disruption, and yogurt systems showed a solid state, which was consistent with the results of Skytte et al. (2015). With the increase of frequency, tan δ decreased first and then increased, indicating that the elastic components were lost and the viscous components were gradually increased in the solid‐like yogurt system, and the elastic behavior of yogurt was gradually weakened, whereas the viscous behavior was enhanced (Zhao et al., 2013).…”
Section: Resultssupporting
confidence: 91%
“…Pictures were acquired at a resolution of 1024 × 1024 using the Leica LAS AF 2.7.3 software (Leica Microsystems GmbH, Wetzlar, Germany). For image texture analysis, grey level co‐occurrence (GLC) matrices (Fagan et al , ; Skytte et al , ) were generated from grey scale 8‐bit images using version 0.4 plugin in Fiji (ImageJ Version 1.49b, http://www.fiji.sc).…”
Section: Methodsmentioning
confidence: 99%
“…Then, they were washed with distilled water three times. All micrographs were captured using the modified method of Skytte et al (2015). A Leica DM IRE2 confocal scanning laser microscope (Leica Microsystems, Heidelberg, Germany) and a 40 × oil immersion objective (40 × HCX PL Apo 1.25 Oil) were used.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%